2012
DOI: 10.1080/02626667.2011.633916
|View full text |Cite
|
Sign up to set email alerts
|

Hydroclimate variability and long-lead forecasting of rainfall over Thailand by large-scale atmospheric variables

Abstract: The development of statistical relationships between local hydroclimates and large-scale atmospheric variables enhances the understanding of hydroclimate variability. The rainfall in the study basin (the Upper Chao Phraya River Basin, Thailand) is influenced by the Indian Ocean and tropical Pacific Ocean atmospheric circulation. Using correlation analysis and cross-validated multiple regression, the large-scale atmospheric variables, such as temperature, pressure and wind, over given regions are identified. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 48 publications
(57 reference statements)
1
10
0
Order By: Relevance
“…With respect to the observed 1961-1990 average MJJ rainfall, abovenormal rainfall will tend to occur during the 2020s and 2070s, whereas below-normal rainfall will tend to occur during the remaining periods. The increasing trend of rainfall in particular during the 2020s is consistent with Tao et al (2003), who presented the effects of climate change on increasing annual rainfall in Thailand, Singapore, Vietnam, and Laos. Under the B2 scenario, the maximum MJJ rainfall (600.2 mm) will be found in 2022, corresponding to an anomaly of +1.86 mm.…”
Section: Annual Variability and Trendsupporting
confidence: 64%
“…With respect to the observed 1961-1990 average MJJ rainfall, abovenormal rainfall will tend to occur during the 2020s and 2070s, whereas below-normal rainfall will tend to occur during the remaining periods. The increasing trend of rainfall in particular during the 2020s is consistent with Tao et al (2003), who presented the effects of climate change on increasing annual rainfall in Thailand, Singapore, Vietnam, and Laos. Under the B2 scenario, the maximum MJJ rainfall (600.2 mm) will be found in 2022, corresponding to an anomaly of +1.86 mm.…”
Section: Annual Variability and Trendsupporting
confidence: 64%
“…To reveal the relationship between the rainfall activity during the pre-monsoon period and the start of monsoon circulation, a heat budget analysis for the area above the Indochina Peninsula during the pre-monsoon period is required. Recently, Singhrattna et al (2012) tried to forecast rainfall amount over Thailand using statistical approach. Their model presents better performance in pre-monsoon rainfall in dry years compared to wet years, in particular, at the lead time of 5-6 months, and vice versa for monsoon rainfall.…”
Section: Moisture In the Pre-monsoon Seasonmentioning
confidence: 99%
“…Comparisons between meteorological data sets for Thailand and Pacific Ocean El Niño events have, for example, shown that summer monsoon precipitation over Thailand decreases as a result of El Niño events, leading to relatively drier conditions (Bridhikitti, 2013;Hsu et al, 2014;Loo et al, 2014;Singhrattna et al, 2005Singhrattna et al, , 2012 and more enriched isotopic values. The opposite is the case during La Niña events.…”
Section: Controls On δD Precipitation and δD Wax In Thailandmentioning
confidence: 99%